INFOGEST inter-laboratory recommendations for assaying gastric and pancreatic lipases activities prior to in vitro digestion studies. (July 2021) - Grundy, Myriam M.L.; Abrahamse, Evan; Almgren, Annette; Alminger, Marie; Andres, Ana; Ariëns, Renata M.C.; Bastiaan-Net, Shanna; Bourlieu-Lacanal, Claire; Brodkorb, André; Bronze, Maria R.; Comi, Irene; Couëdelo, Leslie; et al.
Graphical abstract: Highlights: Lipases activities have to be determined prior to in vitro lipid digestion studies. The pH-stat method gives reproducible data within individual laboratory. pH-stat equipment parameters need to be considered to limit inter-laboratory variability. The reaction vessel shape significantly impacted the reproducibility of the results. Boronic acid is not efficient at inhibiting gastric lipase. Abstract: In vitro digestion studies often use animal digestive enzyme extracts as substitutes of human gastric and pancreatic secretions. Pancreatin from porcine origin is thus commonly used to provide relevant pancreatic enzymes such as proteases, amylase and lipase. Rabbit gastric extracts (RGE) have been recently introduced to provide gastric lipase in addition to pepsin. Before preparing simulated gastric and pancreatic extracts with targeted enzyme activities as described in in vitro digestion protocols, it is important to determine the activities of enzyme preparations using validated methods. The purpose of this inter-laboratory study within the INFOGEST network was to test the repeatability and reproducibility of lipase assays using the pH-stat technique for measuring the activities of gastric and pancreatic lipases from various sources. Twenty-one laboratories having different pH-stat devices received the same protocol with identical batches of RGE and two pancreatin sources. Lipase assays were performed using tributyrin as a substrate and three different amounts (50, 100 and 200 µg) of each enzyme preparation. The repeatability results within individual laboratories were satisfactory with coefficients of variation (CVs) ranging from 4 to 8% regardless of the enzyme amount tested. However, the inter-laboratory variability was high (CV > 15%) compared to existing standards for bioanalytical assays. We identified and weighted the contributions to inter-laboratory variability of several parameters associated with the various pH-stat equipment used in this study (e.g. reaction vessel volume and shape, stirring mode and rate, burette volume for the automated delivery of sodium hydroxide). Based on this, we established recommendations for improving the reproducibility of lipase assays using the pH-stat technique. Defining accurate and complete recommendations on how to correctly quantify activity levels of enzyme preparations is a gateway to promising comparison of in vitro data obtained from different laboratories following the same in vitro digestion protocol.